Public narratives and attitudes towards refugees and other migrants: Hungary country profile - Amanda Gray Meral; Claire Kumar (ODI Global, 2025)
Hungary has a long history of movement across its borders. Under the Habsburg Empire Germans, Slavs, Italians, Romanians and Jews lived in or transited through the country. Following the First World War and the Treaty of Trianon in 1920, Hungary lost more than two-thirds of its territory and people. Overnight millions of Hungarian citizens found themselves living outside of Hungary (Rusu, 2011). Over 2.5 million ethnic Hungarians still live in neighbouring countries, a factor that remains a defining feature of Hungarian national identity (ibid.; Bayer and Rosca, 2020). Ethnic Hungarians living in other countries have received much more favourable treatment under the country's immigration policy, with current legislation providing the right to acquire Hungarian citizenship without any residency in Hungary if the person meets the criteria of Hungarian descent and language proficiency. Under Communist rule Hungary was 'closed', with little migration (Rusu, 2011) (see Figure 1). There were exceptions, such as the migration of around 176,000 Hungarians following the failed revolution against Soviet rule in 1956 (Nemeth and Gruber, 2019, citing Hablicsek and Illes, 2007), the arrival of Greek communists seeking asylum in the 1950s, Chilean communists in the 1970s and students from other communist countries (Rusu, 2011). Hungary also received Cuban weavers, Polish miners and Russian industrial workers (Nemeth and Gruber, 2019, citing Puskas, 1991). Few Hungarians emigrated during the 1990s, but those who did - largely men looking for work or students - mostly went to the US, Germany and Austria. During the same period, many ethnic Hungarians moved to Hungary from bordering countries. Asylum seekers fleeing the war in the former Yugoslavia also found refuge in Hungary, though many either returned to their home country or used Hungary as a transit route to Western Europe (Rusu, 2011).
Keywords: 320